Comparison of the Egg Characteristics of Different Sudanese Indigenous Chicken Types - Mohammed, Mekki Dafaalla; Abdalsalam, Yousif I brahimm; Kheir, Abdelrahman Mohammed; Jin-yu, Wang; Hussein, Musa Hassan (International Journal of Poultry Science, 2005)
Three local types of Sudanese indigenous fowls, large Baladi (LB), Bare-neck (BN) and Betwil (BT) were studied for detection of maturity live weight and egg characteristics. The (BN) average live weight (1547.2±274.5 gm) was heavier than either (LB) (1494.4±349.8 gm) or (BT) (1198.3±257.5 gm), The Betwil average live weight is significantly (P< 0.05) lighter than those of other two local types. The weekly hen-day egg production means were 3.7, 3.2 and 3.9 for (BN), (BT) and (LB) respectively, while the corresponding hen-housed egg production means were 3.3, 2.7 and 3.4. The rate of egg production during the laying period (36 weeks) was 47.14, 38.57 and 48.57 for (BN), (BT) and (LB) respectively. There were significant differences (P< 0.05) in average egg-shell thickness among local types. The means of egg-shell thickness for (BT) and (BN), 36.2±4.2 and 36.2±4.0μrespectively were similar and both significantly thicker than that of (LB), 34.3±3.6μ